2010
DOI: 10.1249/mss.0b013e3181ae2bc0
|View full text |Cite
|
Sign up to set email alerts
|

ACTN3 and ACE Genotypes in Elite Jamaican and US Sprinters

Abstract: Given that ACTN3 XX genotype is negatively associated with elite sprint athlete status, the underlying low frequency in these populations eliminates the possibility of replicating this association in Jamaican and US African American sprinters. The finding of no excess in ACE DD or GG genotypes in elite sprint athletes relative to controls suggests that ACE genotype is not a determinant of elite sprint athlete status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
0
8

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 41 publications
6
88
0
8
Order By: Relevance
“…Indeed, because gains were greatest for RR and least for RX or XX polymorphisms, a trend for a dose response in the R577X genotype was observed in the present study. These findings are consistent with previous reports indicating that alpha-actinin-3 deficiency appears to impair muscle performance (in different population studies) (Clarkson et al 2005;Scott et al 2010;Judson et al 2011). Recent research (Seto et al 2011) concluded that genotype differences in fast muscle force production result in fast-twitch fibers developing slower properties, suggesting that the lack of alpha-actinin-3 may cause faster decline in muscle function with increasing age.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, because gains were greatest for RR and least for RX or XX polymorphisms, a trend for a dose response in the R577X genotype was observed in the present study. These findings are consistent with previous reports indicating that alpha-actinin-3 deficiency appears to impair muscle performance (in different population studies) (Clarkson et al 2005;Scott et al 2010;Judson et al 2011). Recent research (Seto et al 2011) concluded that genotype differences in fast muscle force production result in fast-twitch fibers developing slower properties, suggesting that the lack of alpha-actinin-3 may cause faster decline in muscle function with increasing age.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, with the present design for phenotype assessment, the hypothesis that ACE I/D and ACTN3 R557X genotypes might exert a combined influence on leg muscle phenotypes was not corroborated. Though controversy exists (McCauley et al 2009(McCauley et al , 2010Moran et al 2006), the ACE D allele has been associated with power-related phenotypes in non-athletic populations (Giaccaglia et al 2008;Hopkinson et al 2004;Yamin et al 2007); this allele has also been associated with elite "sprint" athletic performance (Myerson et al 1999;Woods et al 2001), though more recent data do not corroborate such association Scott et al 2005Scott et al , 2010. However, the association between leg 'explosive' muscle power and the ACE I/D polymorphism had not been studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, sua deficiência parece beneficiar o desempenho em provas de longa duração 9,15 . Além disso, a etnia da população analisada deve ser levada em conta em estudos de associação do gene ACTN3 com o desempenho esportivo 40 . Contudo, a influência da α-actinina-3 no desempenho em provas de longa duração ainda necessita de mais investigações.…”
Section: Considerações Finaisunclassified
“…Por outro lado, Scott et al 40 não verificaram diferenças de frequência do genótipo XX entre atletas velocistas e indivíduos não-atletas. Foram analisados velocistas de elite jamaicanos (AJ) e norte-americanos (ANA) comparados a indiví-duos controle também jamaicanos (CJ) e norte--americanos (CNA).…”
unclassified
See 1 more Smart Citation